PENGEMBANGAN MEDIA BUKU CERITA DIGITAL PADA MATERI HAK DAN KEWAJIBAN UNTUK MENINGKATKAN CIVIC KNOWLEDGE SISWA KELAS IV SD - Nanda Alyya Riftina Azmi; Dinie Anggraeni Dewi; Agil Nanggala (STKIP Subang, 2026)
This study was motivated by elementary school students' low level of civic knowledge regarding rights and obligations and the limited use of digital learning media capable of presenting learning materials in a contextual and engaging manner. The study aimed to develop a Book Creator-based digital storybook on the topic of rights and obligations, determine the feasibility of the developed media, describe teachers' and students' responses to the media, and examine its effectiveness in improving fourth-grade students' civic knowledge. This study employed the Design and Development (D&D) method using the ADDIE model, consisting of the analysis, design, development, implementation, and evaluation stages. The participants were one fourth-grade teacher and 22 fourth-grade students at SDN Percobaan. Data were collected through interviews, observations, documentation, expert validation questionnaires, teacher and student response questionnaires, and pretest and posttest instruments. The data were analyzed using descriptive quantitative and qualitative techniques, while the effectiveness of the media was examined using the N-Gain test, normality test, and t-test. The findings indicated that the digital storybook was categorized as highly feasible based on evaluations from subject matter, media, and language experts. Teachers' and students' responses were also categorized as very positive. Furthermore, the findings demonstrated that the digital storybook effectively improved students' civic knowledge, as reflected by higher posttest scores than pretest scores, a moderate N-Gain category, and a statistically significant difference between students' learning outcomes before and after the implementation of the media. Therefore, the Book Creator-based digital storybook is feasible and effective as a learning medium for Pancasila Education on the topic of rights and obligations in elementary schools.